Hubungan Dukungan Keluarga Dan Kepemimpinan Keluarga Dengan Pelaksanaan Footcare Pada Penderita Diabetes Melitus Diwilayah Kerja Puskesmas Sawah Lebar Kota Bengkulu Tahun 2025 - Hero Pratama Inzagi; Danur Azissah; Hengki Tranado (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Diabetes mellitus is a chronic disease that requires continuous management to prevent complications, including foot complications. Proper footcare can prevent wounds and amputations in people with diabetes mellitus. Data from the Sawah Lebar Community Health Center (Puskesmas) area shows that some people with diabetes mellitus still do not practice optimal footcare. This study aims to determine the relationship between family support and family leadership and footcare practices among people with diabetes mellitus in the Sawah Lebar Community Health Center area in Bengkulu City. This study used a descriptive analytical method with a cross-sectional design. The sample consisted of 72 respondents with diabetes mellitus, selected using a random sampling technique. Family support and leadership were measured using a questionnaire, while footcare practices were also measured using a questionnaire for those with diabetes mellitus. Data were analyzed using univariate and bivariate methods using the chi-square test at a significance level of α = 0.05. The results showed that most respondents received good family support, had good family leadership, and practiced footcare in the moderate to good category. Bivariate analysis results showed a significant relationship between support and footcare implementation, as well as leadership and footcare implementation in patients with diabetes mellitus. This study recommends that community health centers (Puskesmas) improve health education that involves families.